Biodigestão anaeróbica de dejetos de suínos e aves associado ao uso de inoculantes - TELES, Ismar Batista (2019)
Several studies have been carried out aiming at the increase and production of biogas, being the association of substrates a very researched method. However, it is important to aggregate processes to optimize biodigestion. Thus, the addition of microorganisms aims to accelerate the onset of fermentation, reducing the period of bacterial colonization. Faced with this, it was objectified with this research was to analyze the dynamics and efficiency of anaerobic biodigestion, using two substrates, swine manure and co-substrate of excreta from laying hens associated to different inoculants, under the perspective of reduction of solids, coliforms and production of biogas. The experiment was conducted from November to December 2018, at the Federal Institute of Science and Technology Education of the South of Minas Gerais - Campus Machado, in the city of Machado – MG. The experimental design was a randomized block design, in a factorial scheme (2 substrates x 3 inoculants), with four replicates per treatment, thus totaling 24 bench biodigesters. Biodigestion was performed for 40 days at the average ambient temperature, 23°C. The efficiency of the biodigestion process was evaluated by reductions of total solids, volatile solids, chemical oxygen demand, biochemical oxygen demand, most probable number of total and fecal coliforms, as well as production and biogas and methane production potentials. The use of co-substrate of laying hens with swine manure promoted a higher initial biogas production when submitted to anaerobic biodigestion, but presented less efficient reductions in solids contents and in biogas production potential per kg of total solids. The levels of methane generated from swine + poultry and swine were 69% and 72%, respectively. No change was observed in the production of biogas due to the addition of microorganisms.